2018
DOI: 10.2174/1389201019666180718094334
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of G-CSF Prevent Cerebral Infarction and Maintain Muscle Strength in an Experimental Model of Global Ischemic Stroke

Abstract: The results indicate a neuroprotective effect of G-CSF, even in small doses, in mice subjected to global cerebral ischemia, thereby reducing the neurofunctional impairment caused by stroke, when considering the maintenance of muscle strength in the treated animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent research has demonstrated the neuroprotective impact of G-CSF treatment, which is due to its high antioxidant, anti-inflammatory, and antiapoptotic properties [10,11]. In a number of ischemic rodent models, G-CSF has been demonstrated to provide long-term neuroprotection by encouraging somatic growth and improving sensorimotor and neurocognitive skills [70,71]. The neuro-regenerative and neuroprotective properties of G-CSF have also been demonstrated in preclinical studies in a number of neurodevelopmental disorders, including autism, spinal cord injury, cerebral ischemia, PD, and AD [5,10,[72][73][74].…”
Section: Neuroprotective Properties Of Granulocyte Colony-stimulating...mentioning
confidence: 99%
“…Recent research has demonstrated the neuroprotective impact of G-CSF treatment, which is due to its high antioxidant, anti-inflammatory, and antiapoptotic properties [10,11]. In a number of ischemic rodent models, G-CSF has been demonstrated to provide long-term neuroprotection by encouraging somatic growth and improving sensorimotor and neurocognitive skills [70,71]. The neuro-regenerative and neuroprotective properties of G-CSF have also been demonstrated in preclinical studies in a number of neurodevelopmental disorders, including autism, spinal cord injury, cerebral ischemia, PD, and AD [5,10,[72][73][74].…”
Section: Neuroprotective Properties Of Granulocyte Colony-stimulating...mentioning
confidence: 99%